Method for regulating and controlling geometric conformation of food-grade two-phase liquid drops through nanoparticle mediated liquid drop phagocytosis mechanism

The geometric conformation of food-grade biphasic droplets is regulated through the nanoparticle-mediated droplet phagocytosis mechanism, which solves the problems of low regulation efficiency and high cost in the prior art, and achieves efficient and low-cost biphasic droplet preparation and stability guarantee.

CN119733452AActive Publication Date: 2025-04-01OCEAN UNIV OF CHINA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510021106.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-01
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the geometric conformation of food-grade biphasic droplets, and the microfluidic control technology is inefficient and costly to prepare biphasic droplets, which is not conducive to large-scale production.

Method used

Through the nanoparticle-mediated droplet phagocytosis mechanism, it affects the interface structure of sodium alginate droplets and zein protein droplets, and realizes the regulation of the geometric conformation of food-grade biphasic droplets. Specific methods include deamidating zein, grafting with sodium alginate through Maillard reaction to form nanoparticles, and emulsifying by vortex method to regulate the geometric conformation of the droplets.

Benefits of technology

Effective regulation of the geometric conformation of food-grade biphasic droplets is achieved, and large-scale preparation of Janus droplets or core-shell droplets is possible, reducing production costs, improving efficiency, and ensuring product biocompatibility and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733452A_ABST
    Figure CN119733452A_ABST
Patent Text Reader

Abstract

The invention discloses a method for regulating and controlling geometric conformation of food-grade two-phase liquid drops through a nanoparticle mediated liquid drop phagocytosis mechanism, and belongs to the technical field of nanometer materials. The molecular structure of the zein is broken through the deamidation effect, and the amphipathy of the zein is further improved through the Maillard reaction, so that the nano-particles with flexible conformation are constructed. The nano-particles are dispersed into a sodium alginate solution, the nano-particles, a zein solution and medium-chain triglyceride are prepared into the two-phase liquid drops based on a vortex method, and effective control over a Janus structure or a core-shell structure of the two-phase liquid drops can be achieved. According to the method for regulating and controlling the geometric conformation of the food-grade two-phase liquid drops, nano-particles are easy to prepare, the geometric conformation of the two-phase liquid drops is easy to regulate and control, large-scale preparation can be achieved, and meanwhile the material for constructing the two-phase liquid drops has good biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a method for regulating the geometric conformation of food-grade two-phase droplets through a nanoparticle-mediated droplet engulfment mechanism. Background Art

[0002] Traditional single-phase droplets have been widely studied, which have a single interface and chamber, but they cannot meet complex application requirements. In contrast, biphasic droplets are composed of two mutually incompatible dispersed phases and have multiple interfaces and compartments, which are conducive to meeting complex application requirements. Existing biphasic droplets are usually prepared using microfluidic technology, which has low preparation efficiency and high cost, and is not conducive to large-scale production. The collision between incompatible droplets provides an opportunity for the formation of biphasic droplets and multiple interfaces. Due to the Marangoni effect, droplets with lower interfacial tension tend to spread on the surface of droplets with higher interfacial tension. The interface evolution during the collision of incompatible droplets leads to the formation of biphasic droplets with water-water interfaces. However, surfactants cannot be stably adsorbed on the interface, but are in a dynamic adsorption-desorption process. In contrast, particulate emulsifiers have excellent interfacial activity and exhibit irreversible adsorption behavior on the interface. Therefore, the conformation of biphasic droplets can be controlled by controlling the interface of incompatible droplets stabilized by nanoparticles. It is necessary to develop nanoparticles with a specific structure and regulate the geometric conformation of biphasic droplets based on the phagocytosis of droplets.

[0003] As shown in the following patent: Application number: CN202010569775.6, Publication number: CN111701627A, the invention name is "A device and method for rapid generation of core-shell droplets based on surface acoustic wave microfluidics", which discloses a method for preparing core-shell droplets. This method can be used to prepare core-shell droplets, but the size of the droplets will be limited by the microfluidic device, and the preparation of smaller core-shell droplets cannot be achieved. In addition, microfluidic equipment has a high cost, and the production efficiency is also limited by the pores of the microfluidic chip, which is inefficient and not conducive to the large-scale preparation of core-shell droplets.

[0004] As shown in the following patent: Application number: CN201711155312.X, Publication number: CN109806918A, Invention name: "Preparation method of gelatin methacrylamide core-shell microspheres based on microfluidic technology", a method for preparing core-shell droplets and particles is disclosed. This method uses methyl cellulose and gelatin methacrylamide based on microfluidic technology to prepare core-shell droplets, but the final particle size of the core-shell droplets is about 200 um. The larger particle size is not conducive to the stability of the core-shell droplets and subsequent applications. In addition, the core-shell droplets are composed of methacrylamide, which is toxic and cannot be used in industries such as food, medicine and cosmetics.

[0005] The article "Batch-scale preparation of reverse Janus emulsions" discloses a technology for the large-scale preparation of Janus droplets. This method uses sodium carbonate and ethanol as mutually incompatible dispersed phases, constructs Janus droplets in batches by vortexing, and achieves the regulation of the geometry of Janus droplets. However, the presence of ethanol in the droplets may be detrimental to their application in food. In addition, this method cannot adjust the droplets to a core-shell conformation.

[0006] As mentioned above, there is still a lack of a method to regulate the geometric conformation of food-grade biphasic droplets and to prepare them on a large scale. Therefore, it is urgent to develop a method to efficiently regulate the structure of biphasic droplets. Currently, nanoparticles can regulate the interface structure of droplets, but there is no report on a method to regulate the geometric conformation of biphasic droplets by affecting the phagocytosis of droplets. Summary of the invention

[0007] The main purpose of the present invention is to provide a method for regulating the geometric conformation of food-grade two-phase droplets by a nanoparticle-mediated droplet engulfment mechanism and to prepare a food-grade two-phase droplet, so as to overcome the shortcomings of the prior art.

[0008] The principle of the present invention is to affect the phagocytosis of zein droplets based on the regulation of the interface structure of sodium alginate droplets by nanoparticles, and realize the effective control of the geometric conformation of food-grade two-phase droplets. First, zein is deamidated to break the molecular structure of zein, and then sodium alginate is grafted on protein through Maillard reaction, and the conjugate is further assembled to form deamidated zein-sodium alginate nanoparticles. In addition, zein-sodium alginate nanoparticles are constructed through Maillard reaction. Nanoparticles are dispersed in sodium alginate solution, and the geometric conformation of two-phase droplets is regulated by mixing and emulsifying zein, sodium alginate solution and MCT solution containing PGPR. The adsorption of nanoparticles at the interface of sodium alginate and MCT will form an interfacial film of different structures, and the strength of the interfacial film will affect the phagocytosis of zein droplets on sodium alginate droplets, thereby affecting the geometric conformation of two-phase droplets, and finally realizing the effective control of Janus droplets and core-shell droplets.

[0009] In order to achieve the technical purpose of the present invention, the technical solution of the present invention includes the following steps:

[0010] (1) Disperse zein in deionized water and adjust the pH of the solution to obtain a zein stock solution.

[0011] (2) The zein solution is heated to obtain a deamidated zein solution.

[0012] (3) preparing a sodium alginate solution, adding the sodium alginate solution to the zein solution or the deamidated zein solution obtained in step (1) or (2), heating the zein solution containing sodium alginate, and cooling to obtain a zein-sodium alginate nanoparticle dispersion or a deamidated zein-sodium alginate nanoparticle dispersion.

[0013] (4) Biphasic droplets were constructed based on zein solution, sodium alginate solution and medium-chain triglycerides (MCT).

[0014] (5) Dispersing the nanoparticles into the sodium alginate solution obtained in step (4).

[0015] (6) Dissolve polyglycerol ricinoleate (PGPR) in MCT.

[0016] (7) Zein solution, sodium alginate solution containing nanoparticles, and MCT solution containing PGPR were added in proportion and biphasic droplets were prepared by vortexing.

[0017] Preferably, the concentration of zein in the zein solution in step (1) is 10 wt %, and the pH value of the solution is 12.0;

[0018] Preferably, in step (2), the heating temperature is 80°C and the heating time is 10 h;

[0019] Preferably, in step (3), the concentration of the sodium alginate solution is 2 wt %, and the pH of the solution is 12.0;

[0020] Preferably, in step (3), the concentration of the zein solution or the deamidated zein solution is 2 wt %, and the pH of the solution is 12.0;

[0021] Preferably, in step (3), the mixing ratio of the sodium alginate solution to the zein solution or the deamidated zein solution is 1:1;

[0022] Preferably, in step (3), the sodium alginate solution and the zein solution or the deamidated zein solution are mixed and heated at a temperature of 80° C. for a heating time of 3.5 h;

[0023] Preferably, in step (4), the concentration of the zein solution is 10 wt %, and the pH value of the solution is 12.0. The concentration of the sodium alginate solution is 1.5 wt %, and the pH value of the solution is 12.0.

[0024] Preferably, in step (5), the concentration of the nanoparticles in sodium alginate is 1.5 mg / mL or 3 mg / mL;

[0025] Preferably, in step (6), the concentration of PGPR is 2 wt %;

[0026] Preferably, in step (7), the ratio of zein solution, sodium alginate solution and MCT is 2:1:7;

[0027] Preferably, in step (7), the vortex speed is 3000 rpm and the vortex time is 3 min.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention uses zein as one of the raw materials for constructing nanoparticles, which can still maintain an aggregated spherical structure in an alkaline environment. After zein is grafted with sodium alginate, the particle size of the nanoparticles is significantly reduced due to the increase in hydrophilicity, which can play a beneficial role of the nanoparticles at the oil-water interface. In addition, zein is broken into polypeptides through deamidation treatment, which are then grafted with sodium alginate through the Maillard reaction to form nanoparticles. The particles have a flexible conformation, which is conducive to rearrangement at the oil-water interface to form a complete interface structure, thereby regulating the phagocytosis of zein droplets.

[0030] (2) The present invention is the first to use nanoparticles to regulate the geometric conformation of biphasic droplets. The adsorption and rearrangement behavior of nanoparticles on the interface of sodium alginate droplets will significantly change the interface structure, and exhibit significant strain hardening behavior during the interface compression process, which helps to maintain the interface structure, thereby affecting the phagocytosis of zein droplets on sodium alginate droplets, and ultimately achieving effective regulation of the geometric conformation of biphasic droplets.

[0031] (3) The zein, sodium alginate, medium-chain triglycerides, and polyglycerol ricinoleate used in the present invention are all food-grade raw materials, and no other substances are introduced in the process of nanoparticle construction. The constructed two-phase droplets have good biocompatibility and do not produce toxic and harmful substances. Therefore, they can be used in the fields of food, medicine, and cosmetics.

[0032] (4) The present invention innovatively proposes the engulfment behavior between incompatible droplets. Driven by the Marangoni force, the zein droplets will engulf the sodium alginate droplets, which is similar to the phagocytosis of macrophages in the human body. This can better understand the formation process of biphasic droplets and regulate the droplet engulfment process, which is conducive to controlling the geometric conformation of biphasic droplets.

[0033] (5) The one-step emulsification method used in the present invention can prepare Janus droplets or core-shell droplets on a large scale, and has the beneficial effects of low cost and high efficiency compared to microfluidic technology.

[0034] (6) The two-phase droplets prepared by the present invention have a smaller particle size and exhibit good stability, which is conducive to maintaining stability in various application scenarios.

[0035] (7) The nanoparticles used in the present invention are easy to prepare. The organic combination of deamidation and Maillard reaction allows zein and sodium alginate to form nanoparticles with different structures. The reaction is efficient and safe. At the same time, the nanoparticles are endowed with better interfacial activity, which can effectively regulate the phagocytosis between incompatible droplets. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 1 and 2 are transmission electron micrographs of zein-alginate nanoparticles (ZSNPs) (a) in Example 1 and deamidated zein-alginate nanoparticles (DZSNPs) (b) in Example 3.

[0037] Figure 2 The SDS-PAGE patterns of zein (Zein), deamidated zein (DZein), zein-sodium alginate nanoparticles (ZSNPs) and deamidated zein-sodium alginate nanoparticles (DZSNPs) in Examples 2 and 4 are shown.

[0038] Figure 3 is the grafting degree of zein-sodium alginate nanoparticles (ZSNPs) and deamidated zein-sodium alginate nanoparticles (DZSNPs) in Example 1 and Example 3.

[0039] Figure 4 Example 1 and Example 3 are the free amino content of the samples before and after the Maillard reaction.

[0040] Figure 5 Example 1 and Example 3 are the absorbance of the samples before and after the Maillard reaction at 420 nm.

[0041] Figure 6 Example 1 and Example 3 are the absorbance of the samples before and after the Maillard reaction at 304 nm.

[0042] Figure 7 These are the intrinsic fluorescence spectra of zein (Zein), deamidated zein (DZein), zein-sodium alginate nanoparticles (ZSNPs) and deamidated zein-sodium alginate nanoparticles (DZSNPs) in Examples 2 and 4.

[0043] Figure 8These are Fourier transform infrared spectra of zein (Zein), deamidated zein (DZein), zein-sodium alginate nanoparticles (ZSNPs) and deamidated zein-sodium alginate nanoparticles (DZSNPs) in Examples 2 and 4.

[0044] Fig. 9 These are Raman spectra of zein (Zein), deamidated zein (DZein), zein-sodium alginate nanoparticles (ZSNPs) and deamidated zein-sodium alginate nanoparticles (DZSNPs) in Examples 2 and 4.

[0045] Fig.10 It is the protein secondary structure content of zein (Zein), deamidated zein (DZein), zein-sodium alginate nanoparticles (ZSNPs) and deamidated zein-sodium alginate nanoparticles (DZSNPs) in Example 2 and Example 4.

[0046] Fig.11 These are the disulfide bond conformations of zein (Zein), deamidated zein (DZein), zein-sodium alginate nanoparticles (ZSNPs) and deamidated zein-sodium alginate nanoparticles (DZSNPs) in Examples 2 and 4.

[0047] Fig.12 It is the I850 / I830 of zein (Zein), deamidated zein (DZein), zein-sodium alginate nanoparticles (ZSNPs) and deamidated zein-sodium alginate nanoparticles (DZSNPs) in Examples 2 and 4.

[0048] Fig.13 The effects of the content and structure of nanoparticles on the morphology of biphasic droplets in Examples 1-4; low zein-alginate nanoparticle addition amount (ZSNPs-L) (a), high zein-alginate nanoparticle addition amount (ZSNPs-H) (b), low deamidated zein-alginate nanoparticle addition amount (DZSNPs-L) (c), high deamidated zein-alginate nanoparticle addition amount (DZSNPs-H) (d).

[0049] Fig.14 The effect of the content and structure of nanoparticles on the curvature of the two-phase droplet interface in Examples 1-4.

[0050] Fig.15Cryo-scanning electron micrographs of zein droplets (ab), sodium alginate droplets (cd), Janus droplets (ef) and core-shell droplets (gh) in Examples 3-6.

[0051] Fig.16 Effect of nanoparticles on the interfacial structure of sodium alginate droplets; low zein-alginate nanoparticle addition amount (ZSNPs-L) (a), high zein-alginate nanoparticle addition amount (ZSNPs-H) (b), low deamidated zein-alginate nanoparticle addition amount (DZSNPs-L) (c), high deamidated zein-alginate nanoparticle addition amount (DZSNPs-H) (d).

[0052] Fig.17 Lissajous plots of alginate droplets containing nanoparticles at 30% amplitude; low zein-alginate nanoparticle addition amount (ZSNPs-L) (a), high zein-alginate nanoparticle addition amount (ZSNPs-H) (b), low deamidated zein-alginate nanoparticle addition amount (DZSNPs-L) (c), high deamidated zein-alginate nanoparticle addition amount (DZSNPs-H) (d).

[0053] Fig.18 This is the interfacial viscoelastic modulus-amplitude curve of sodium alginate droplets containing nanoparticles.

[0054] Fig.19 TSI curve of sodium alginate droplets containing nanoparticles.

[0055] Fig. 20 The effect of nanoparticles on TSI of biphasic droplets. DETAILED DESCRIPTION

[0056] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0057] Operations not mentioned in the present invention are all routine operations in the art, and materials whose specific sources are not mentioned in the present invention are all conventional materials that can be purchased from the market.

[0058] Example 1

[0059] (1) Prepare a 10 wt% zein solution and adjust its pH to 12.0 to obtain a zein stock solution. Dilute the zein solution to 2 wt%. Prepare a 2 wt% sodium alginate solution and adjust its pH to 12.0. Mix the zein solution and the sodium alginate solution in a ratio of 1:1. Heat the mixed solution at 80°C for 3.5 h to obtain zein-sodium alginate nanoparticles.

[0060] (2) Prepare 10 wt% zein solution and 1.5 wt% sodium alginate solution, and adjust the pH of the solution to 12.0. Prepare an MCT solution containing 2 wt% PGPR. Disperse zein-sodium alginate nanoparticles in the sodium alginate solution at a particle concentration of 1.5 mg / mL.

[0061] (3) The zein solution, sodium alginate solution containing nanoparticles, and MCT solution were vortexed in a ratio of 2:1:7 at 3000 rpm for 3 min to prepare biphasic droplets.

[0062] Example 2

[0063] (1) Prepare a 10 wt% zein solution and adjust its pH to 12.0 to obtain a zein stock solution. Dilute the zein solution to 2 wt%. Prepare a 2 wt% sodium alginate solution and adjust its pH to 12.0. Mix the zein solution and the sodium alginate solution in a ratio of 1:1. Heat the mixed solution at 80°C for 3.5 h to obtain zein-sodium alginate nanoparticles.

[0064] (2) Prepare 10 wt% zein solution and 1.5 wt% sodium alginate solution, and adjust the pH of the solution to 12.0. Prepare an MCT solution containing 2 wt% PGPR. Disperse zein-sodium alginate nanoparticles in the sodium alginate solution at a particle concentration of 3 mg / mL.

[0065] (3) The zein solution, sodium alginate solution containing nanoparticles, and MCT solution were vortexed in a ratio of 2:1:7 at 3000 rpm for 3 min to prepare biphasic droplets.

[0066] Example 3

[0067] (1) Prepare a 10 wt% zein solution and adjust its pH to 12.0 to obtain a zein stock solution. Heat the 10 wt% zein solution at 80°C for 10 h and cool it to obtain a deamidated zein solution. Dilute the deamidated zein solution to 2 wt%. Prepare a 2 wt% sodium alginate solution and adjust its pH to 12.0. Mix the deamidated zein solution and the sodium alginate solution in a ratio of 1:1. Heat the mixed solution at 80°C for 3.5 h to obtain deamidated zein-sodium alginate nanoparticles.

[0068] (2) Prepare 10 wt% zein solution and 1.5 wt% sodium alginate solution, and adjust the pH of the solution to 12.0. Prepare an MCT solution containing 2 wt% PGPR. Disperse deamidated zein-sodium alginate nanoparticles in the sodium alginate solution at a particle concentration of 1.5 mg / mL.

[0069] (3) The zein solution, sodium alginate solution containing nanoparticles, and MCT solution were vortexed in a ratio of 2:1:7 at 3000 rpm for 3 min to prepare biphasic droplets.

[0070] Example 4

[0071] (1) Prepare a 10 wt% zein solution and adjust its pH to 12.0 to obtain a zein stock solution. Dilute the deamidated zein solution to 2 wt%. Prepare a 2 wt% sodium alginate solution and adjust its pH to 12.0. Mix the zein solution or the deamidated zein solution with the sodium alginate solution in a ratio of 1:1. Heat the mixed solution at 80°C for 3.5 h to obtain deamidated zein-sodium alginate nanoparticles.

[0072] (2) Prepare 10 wt% zein solution and 1.5 wt% sodium alginate solution, and adjust the pH of the solution to 12.0. Prepare an MCT solution containing 2 wt% PGPR. Disperse deamidated zein-sodium alginate nanoparticles in the sodium alginate solution at a particle concentration of 3 mg / mL.

[0073] (3) The zein solution, sodium alginate solution containing nanoparticles, and MCT solution were vortexed in a ratio of 2:1:7 at 3000 rpm for 3 min to prepare biphasic droplets.

[0074] Comparative Example 1

[0075] (1) Prepare a 10 wt% zein solution and adjust its pH to 12.0 to obtain a zein stock solution. Dilute the zein solution to 2 wt%. Prepare a 2 wt% sodium alginate solution and adjust its pH to 12.0. Mix the zein solution and the sodium alginate solution in a ratio of 1:1. Heat the mixed solution at 80°C for 3.5 h to obtain zein-sodium alginate nanoparticles.

[0076] (2) Prepare a 1.5 wt% sodium alginate solution and adjust the pH of the solution to 12.0. Prepare an MCT solution containing 2 wt% PGPR. Disperse zein-sodium alginate nanoparticles in the sodium alginate solution at a particle concentration of 1.5 mg / mL.

[0077] (3) The sodium alginate solution containing nanoparticles and the MCT solution were vortexed in a ratio of 3:7 at a speed of 3000 rpm for 3 min to prepare sodium alginate droplets containing nanoparticles.

[0078] Comparative Example 2

[0079] (1) Prepare a 10 wt% zein solution and adjust its pH to 12.0 to obtain a zein stock solution. Dilute the zein solution to 2 wt%. Prepare a 2 wt% sodium alginate solution and adjust its pH to 12.0. Mix the zein solution and the sodium alginate solution in a ratio of 1:1. Heat the mixed solution at 80°C for 3.5 h to obtain zein-sodium alginate nanoparticles.

[0080] (2) Prepare a 1.5 wt% sodium alginate solution and adjust the pH of the solution to 12.0. Prepare an MCT solution containing 2 wt% PGPR. Disperse zein-sodium alginate nanoparticles in the sodium alginate solution at a particle concentration of 3 mg / mL.

[0081] (3) The sodium alginate solution containing nanoparticles and the MCT solution were vortexed in a ratio of 3:7 at a speed of 3000 rpm for 3 min to prepare sodium alginate droplets containing nanoparticles.

[0082] Comparative Example 3

[0083] (1) Prepare a 10 wt% zein solution and adjust its pH to 12.0 to obtain a zein stock solution. Heat the 10 wt% zein solution at 80°C for 10 h and cool it to obtain a deamidated zein solution. Dilute the deamidated zein solution to 2 wt%. Prepare a 2 wt% sodium alginate solution and adjust its pH to 12.0. Mix the deamidated zein solution and the sodium alginate solution in a ratio of 1:1. Heat the mixed solution at 80°C for 3.5 h to obtain deamidated zein-sodium alginate nanoparticles.

[0084] (2) Prepare a 1.5 wt% sodium alginate solution and adjust the pH of the solution to 12.0. Prepare an MCT solution containing 2 wt% PGPR. Disperse deamidated zein-sodium alginate nanoparticles in the sodium alginate solution at a particle concentration of 1.5 mg / mL.

[0085] (3) The sodium alginate solution containing nanoparticles and the MCT solution were vortexed in a ratio of 3:7 at a speed of 3000 rpm for 3 min to prepare sodium alginate droplets containing nanoparticles.

[0086] Comparative Example 4

[0087] (1) Prepare a 10 wt% zein solution and adjust its pH to 12.0 to obtain a zein stock solution. Heat the 10 wt% zein solution at 80°C for 10 h and cool it to obtain a deamidated zein solution. Dilute the deamidated zein solution to 2 wt%. Prepare a 2 wt% sodium alginate solution and adjust its pH to 12.0. Mix the deamidated zein solution and the sodium alginate solution in a ratio of 1:1. Heat the mixed solution at 80°C for 3.5 h to obtain deamidated zein-sodium alginate nanoparticles.

[0088] (2) Prepare a 1.5 wt% sodium alginate solution and adjust the pH of the solution to 12.0. Prepare an MCT solution containing 2 wt% PGPR. Disperse deamidated zein-sodium alginate nanoparticles in the sodium alginate solution at a particle concentration of 3 mg / mL.

[0089] (3) The sodium alginate solution containing nanoparticles and the MCT solution were vortexed in a ratio of 3:7 at a speed of 3000 rpm for 3 min to prepare sodium alginate droplets containing nanoparticles.

[0090] Comparative Example 5

[0091] (1) A 10 wt% zein solution was prepared and its pH value was adjusted to 12.0 to obtain a zein stock solution.

[0092] (2) Prepare an MCT solution containing 2 wt% PGPR.

[0093] (3) The zein solution and the MCT solution were vortexed in a ratio of 3:7 at a speed of 3000 rpm for 3 min to prepare zein single-phase droplets.

[0094] Comparative Example 6

[0095] (1) Prepare a 1.5 wt% sodium alginate solution and adjust its pH value to 12.0 to obtain a sodium alginate stock solution.

[0096] (2) Prepare an MCT solution containing 2 wt% PGPR.

[0097] (3) The sodium alginate solution and the MCT solution were vortexed in a ratio of 3:7 at a speed of 3000 rpm for 3 min to prepare sodium alginate single-phase droplets.

[0098] Experimental Example 1 Transmission Electron Microscope Observation

[0099] The sample dispersions obtained in Example 1 and Example 3 were dropped onto a copper mesh, and after drying, the morphology of the samples was observed using a transmission electron microscope.

[0100] pass Figure 1 The experimental results show that both samples are spherical nanoparticles, indicating that nanoparticles based on zein and sodium alginate were successfully constructed, and deamidated zein-alginate nanoparticles (DZSNP S ) have a smaller particle size than zein-alginate nanoparticles (ZSNPs).

[0101] Experimental Example 2 SDS-PAGE

[0102] The samples obtained in Example 1 and Example 3 were subjected to electrophoresis. The samples were mixed with the loading buffer and heated in boiling water for 5 min. The electrophoresis was performed using 80 V and 120 V voltages in the stacking gel and the separation gel, respectively, and stained with Coomassie Brilliant Blue R-250.

[0103] pass Figure 2 It can be seen from the experimental results that after the Maillard reaction, the protein band moved up significantly, indicating that sodium alginate was grafted onto the protein through the Maillard reaction.

[0104] Experimental Example 3 Determination of free amino content, grafting degree and Maillard reaction products

[0105] The free amino group content of the samples obtained in Example 2 and Example 4 was determined by the o-phthalaldehyde (OPA) method. The OPA reagent was mixed with the sample and then incubated at 35°C for 2 min. The absorbance at 340 nm was measured using a UV-visible spectrophotometer to calculate the content of free amino acids and the grafting degree of the sample. After the sample was diluted, the absorbance of the sample was measured at 304 nm and 420 nm.

[0106] pass Figure 3-6 The experimental results show that the free amino content is significantly reduced after the Maillard reaction, and the proteoglycan particles have a higher degree of grafting. The content of Maillard reaction products represented by the absorbance at 304 nm and 420 nm is also significantly increased, indicating that the Maillard reaction occurs between protein and polysaccharide.

[0107] Experimental Example 4 Fluorescence Spectrum

[0108] The samples obtained in Example 1 and Example 3 were diluted to a suitable concentration, and the fluorescence spectrum within the range of 300-500 nm was obtained at an excitation wavelength of 280 nm.

[0109] pass Figure 7The experimental results show that the fluorescence intensity of zein increases after deamidation, which may be caused by the unfolding of the protein structure. The fluorescence intensity decreases significantly after the Maillard reaction, which is caused by the rearrangement of the protein structure after the hydrophilic polysaccharide is grafted.

[0110] Experimental Example 5 Fourier Transform Infrared Spectroscopy

[0111] The samples obtained in Example 2 and Example 4 were mixed with potassium bromide and pressed into tablets to obtain 4000-500 cm -1 Fourier transform infrared spectroscopy in the range.

[0112] pass Figure 8 The experimental results show that 3000-3500 cm -1 The characteristic peaks in the range represent C─N and O─H vibrations. After the Maillard reaction, the peaks tend to be flat, which may be caused by the formation of hydrogen bonds. In addition, the infrared spectra of ZSNPs and DZSNPs at 1033 cm -1 A new characteristic peak appeared at , which corresponds to the stretching vibration of the C─O─C bond in sodium alginate, indicating the effective coupling of sodium alginate and zein.

[0113] Experimental Example 6 Raman Spectroscopy

[0114] The Raman spectra of the samples obtained in Example 2 and Example 4 were measured. The spectrum acquisition conditions were: 785 nm, 1800 gr / mm, and the acquisition time and accumulation time were 15 s and 20 times, respectively. The changes in disulfide bond conformation, tyrosine (Tyr) microenvironment, and protein secondary structure were further analyzed.

[0115] pass Fig. 9 The experimental results show that after the Maillard reaction, the -1 A new characteristic peak appeared at the wavelength, which belongs to sodium alginate COO ─ The vibration of the groups indicates the successful grafting of sodium alginate. The changes in the secondary structure of the protein are further analyzed by spectral information, such as Fig.10 As shown in Figure 5, the Maillard reaction resulted in a decrease in the α-helix content and an increase in the β-sheet content, indicating that zein underwent structural unfolding and rearrangement. -1 The changes in the disulfide bond conformation of proteins can be analyzed at different wavelengths, such as Fig.11 As shown in the figure, under high pH conditions, thiol groups are more likely to be deprotonated, thereby increasing the possibility of disulfide bond formation. GGT and GGG are intrachain and interchain disulfide bonds, respectively. The GGT content is significantly reduced after the Maillard reaction, indicating that the breakage of intrachain disulfide bonds is beneficial to improving the flexibility of nanoparticles. The changes in the tyrosine microenvironment in proteins are further analyzed by the I850 / I830 value, as shown in the figure. Fig.12 As shown in the figure, after grafting with sodium alginate, the value of I850 / I830 decreased, indicating that tyrosine was buried inside zein. After grafting with sodium alginate, zein underwent structural rearrangement due to the change in hydrophilicity. This resulted in adjacent tyrosines binding to each other through non-covalent interactions such as hydrogen bonds and π-π stacking.

[0116] Experimental Example 7 Laser Confocal Microscopy

[0117] Laser confocal images of the droplet samples of Examples 1 to 4 were taken. Zein and nanoparticles were labeled with rhodamine B and FITC, respectively, and excited at 561 nm and 488 nm.

[0118] pass Fig.13 The experimental results show that at low particle addition, the biphasic droplets still exhibit Janus structures, and when a high content of DZSNPs is added, the biphasic droplets behave as core-shell droplets. Fig.14 The experimental results also show that the addition of particles significantly affects the interfacial curvature of the two-phase droplets.

[0119] Experimental Example 8 Cryo-Scanning Electron Microscope

[0120] Cryo-scanning electron microscope images of droplet samples of Examples 3 and 4 and Comparative Examples 5 and 6 were taken. The samples were placed on a sample stage and frozen in liquid nitrogen, then transferred to a preparation chamber and fractured, and the samples were sublimated and coated with platinum for morphology observation.

[0121] pass Fig.15 The experimental results show that the single-phase zein droplets ( Fig.15 a and b) and single-phase alginate droplets ( Fig.15 c and d) show obvious differences in network structure. Zein droplets have a denser interface network, while alginate droplets have a loose and porous network structure, which is mainly due to the concentration difference between the two phases. After adding particles, the two-phase droplets appear as Janus droplets ( Fig.15 e and f) and core-shell droplets ( Fig.15 g and h), demonstrating that the addition of nanoparticles can regulate the geometric conformation of biphasic droplets.

[0122] Experimental Example 9 Interfacial behavior of nanoparticles at the oil-water interface.

[0123] The interfacial behaviors of the nanoparticles at the oil-water interface in Comparative Examples 1 to 4 were photographed by laser confocal microscopy, and the interfacial properties of the nanoparticles were determined by interfacial expansion rheology.

[0124] pass Fig.16The experimental results show that the nanoparticles are adsorbed on the oil-water interface, and as the amount of nanoparticles added increases, the content of nanoparticles on the interface increases. When the amount of DZSNPs added is high, the nanoparticles form a complete interface layer at the interface, which may be caused by the better flexibility of DZSNPs and the rearrangement at the interface. Fig.17 The experimental results show that after adding particles, the Lissajous curve becomes asymmetric. This is because the adsorption of nanoparticles affects the interface structure. The interface undergoes strain hardening during compression. It may be that the nanoparticles block the interface, which is conducive to maintaining the interface structure. Fig.18 It can be seen from the experimental results that the addition of nanoparticles affects the interface structure.

[0125] Experimental Example 10 Effect of Nanoparticles on the Stability of Sodium Alginate Droplets

[0126] The stability of the samples of Comparative Examples 1-4 was determined by multiple static light scattering technique. Fig.19 The experimental results show that the addition of nanoparticles enhances the stability of sodium alginate droplets, mainly because the adsorption of nanoparticles at the interface enhances the interfacial film structure.

[0127] Experimental Example 11 Effect of Nanoparticles on the Stability of Biphasic Droplets

[0128] The stability of the samples of Examples 1-4 was determined by multiple static light scattering technique. Fig. 20 The experimental results show that TSI is significantly reduced after the addition of nanoparticles, indicating that the addition of nanoparticles enhances the stability of the two-phase droplets.

Claims

1. A method for regulating the geometric conformation of food-grade biphasic droplets by nanoparticle-mediated droplet engulfment mechanism, characterized in that: The molecular structure of zein was broken by deamidation, and the amphiphilicity of zein was further improved by Maillard reaction, thereby constructing nanoparticles with flexible conformation. The nanoparticles were dispersed in sodium alginate solution, and biphasic droplets were prepared with zein solution and medium-chain triglycerides by vortex method, and the geometric conformation of the biphasic droplets was regulated to Janus structure or core-shell structure.

2. A method for regulating the geometric conformation of food-grade biphasic droplets by nanoparticle-mediated droplet engulfment mechanism, characterized in that: The specific preparation method comprises the following steps: (1) dispersing zein in deionized water and adjusting the pH of the solution to obtain a zein solution; (2) heating the zein solution to obtain a deamidated zein (DZein) solution; (3) preparing a sodium alginate solution, adding the sodium alginate solution to the solution of step (1) or (2) and heating the solution at a temperature of 60-90° C. for a heating time of 1-5 h, and cooling the solution to obtain a zein-alginate nanoparticle (ZSNPs) dispersion or a deamidated zein-alginate nanoparticle (DZSNPs) dispersion; (4) preparing a zein solution and a sodium alginate solution, and constructing biphasic droplets based on the zein solution, the sodium alginate solution and medium-chain triglycerides (MCT); (5) dispersing the nanoparticles prepared in step (3) in the sodium alginate solution prepared in step (4); the concentration of the nanoparticles in the sodium alginate solution is 1-5 mg / mL; (6) dissolving polyglycerol ricinoleate (PGPR) in MCT, with the concentration of PGPR being 1-3 wt %; (7) Zein solution, sodium alginate solution containing nanoparticles, and MCT solution containing PGPR were added in proportion and biphasic droplets were prepared by vortexing.

3. The preparation method according to claim 2, characterized in that include: The zein concentration in the zein solution in step (1) is 6-10 wt %, and the solution pH is 11.5-12.

5.

4. The preparation method according to claim 2, characterized in that include: In step (2), the heating temperature is 60-90°C and the heating time is 2-10 h.

5. The preparation method according to claim 2, characterized in that include: In step (3), the concentration of the sodium alginate solution is 1-2 wt %, and the pH of the solution is 11.5-12.5; The concentration of the zein solution or the deamidated zein solution is 1-2wt%, and the pH value of the solution is 11.5-12.5; the mixing ratio of the sodium alginate solution to the zein solution or the deamidated zein solution is 2:1-1:

2.

6. The preparation method according to claim 2, characterized in that include: In step (4), the concentration of the zein solution is 6-10 wt %, and the pH of the solution is 11.5-12.5; The concentration of sodium alginate solution is 1-2 wt%, and the pH of the solution is 11.5-12.

5.

7. The preparation method according to claim 2, characterized in that include: In step (7), the ratio of zein solution, sodium alginate solution and MCT is 2:1:7 or 1:1:8; the vortex speed is 1000-3000 rpm, and the vortex time is 1-3 min.

8. Food-grade biphasic droplets prepared by the method according to any one of claims 2 to 7.

9. Use of the biphasic droplets according to claim 8 in the fields of food, medicine or cosmetics.

Citation Information

Patent Citations

  • Preparation method of gelatin methacrylamide core-shell microsphere based on microfluidics technique

    CN109806918A

  • Core-shell droplet rapid generation device and method based on acoustic surface wave microfluidic control

    CN111701627A

  • A device and method for rapid generation of core-shell droplets based on surface acoustic wave microfluidics

    CN111701627B

  • Preparation method and application of core-shell structure microcapsule particles

    CN112295514A

  • Preparation method of intestinal targeted slow-release euphausia superba oil Pickering emulsion

    CN116941754A